Highly porous CO2 hydrate generation aided by silica nanoparticles for potential secure storage of CO2 and desalination. Issue 16 (31st January 2017) - Kim, Ijung; Nole, Michael; Jang, Sunghyun; Ko, Saebom; Daigle, Hugh; Pope, Gary A.; Huh, Chun
Abstract : We report a new way of storing CO2 in a highly porous hydrate structure, stabilized by silica nanoparticles (NPs). Abstract : We report a new way of storing CO2 in a highly porous hydrate structure, stabilized by silica nanoparticles (NPs). Such a porous CO2 hydrate structure was generated either by cooling down NP-stabilized CO2 -in-seawater foams, or by gently mixing CO2 and seawater that contains silica NPs under CO2 hydrate-generating conditions. With the highly porous structure, enhanced desalination was also achievable when the partial meltdown of CO2 hydrate was allowed.